African Migrant Learners’ Experiences of Xenophobia in South Africa - Nnadozie, Jude Ifeanyichukwu; Morojele, Pholoho Justice (Journal of Contemporary Issues in Education, 2024)
This article draws on the social identity theory to understand the real life schooling experiences of the migrant learners (from the Democratic Republic of Congo and Zimbabwe) within three South African schools. It adopted a qualitative, narrative research methodology, using open-ended interviews and photovoice as its methods of data collection. The findings reveal complex and pervasive dynamics of xenophobia. These took the form of denigrating stereotypical constructions of African migrants and resulted in the mistreatment, exclusion, and rejection of the African migrant learners. The study recommends further research on issues on African migrant learners schooling experiences in South Africa and for schools to embrace acceptance of African migrant learners for enhancing an inclusive schooling agenda.